La inteligencia interpersonal en el desarrollo del lenguaje oral de los niños y niñas de Educación Inicial II del CECIB Educación Básica Sutipud de la Comunidad Las Granjas del cantón Guamote - Paltán Guaranga, María Hortencia (2019)
The main objective of this study is to determine how interpersonal intelligence influences the development of the oral language of the children of Initial Education II of the CECIB Basic Education “Sutipud” of the community of the Farms of the Guamote Canton, through the application of the “Test of Primary Evaluation. Evaluation of the 8 multiple intelligences” instrument applied to diagnose interpersonal intelligence and the “Test destined to evaluate metalinguistic skills of phonological type (PHMF)” for the assessment of oral language. The methodology used in the research was of mixed order and explanatory-sequential design with two specific types of research such as: field research and bibliographic-documentary research. The main results were that 73% of the population has a regular level of interpersonal intelligence and 26.67% have little presence of intelligence, on the other hand, 57% of children valued are at an average level, 33% It has a low level and 10% with a medium level of oral language development. Finally, through the application of the Chi-square statistical test, it is concluded that interpersonal intelligence significantly influences the development of oral language, since a value of 0.024 was obtained.